High‐Accuracy and Broadband Wavelength Sensor with Detection Region Ranging from Deep Ultraviolet to Near Infrared Light. Issue 2 (2nd November 2021) - Li, Chun‐Yan; Xiao, Yu‐Tian; Fu, Can; Liang, Feng‐Xia; Chen, Li‐Miao; Wu, Di; Luo, Lin‐Bao
Abstract: In this paper, a broadband wavelength sensor which is composed of two horizontally stacked photodetectors is reported. The top part is a monolayer graphene (MLG)/thin Si/MLG heterojunction device and the bottom part is a MLG/Ge Schottky junction device. Owing to the thin thickness of the Si and the wavelength‐dependent absorption coefficients of both Si and Ge, the two photodetectors exhibit sharp contrast in photon‐generation rate when illuminated with different wavelengths of light. This distinction in photon generation leads to completely different evolution in photocurrent, and the corresponding relationship between the photocurrent ratio and wavelength can be easily expressed as a monotonic function, via which the wavelength in a broad range from deep ultraviolet (265 nm) to near infrared light (1550 nm) can be easily calculated. Notably, the average relative error and the average absolute error of the wavelength sensor are estimated to be 2.1% and 2.3 nm, respectively, which are much better than previously reported values. Abstract : A broadband wavelength sensor is composed of two horizontally stacked heterojunction devices. The relationship between the photocurrent ratio of the two devices and the wavelength follows a typical monotonic function through which the wavelength of the incident monochromatic light in a broad range from deep ultraviolet (265 nm) to near infrared light (1550 nm) can be quantitatively determined.